Measles vaccination coverage among five‐year‐old children: implications for disease elimination in Australia - Glenda L. Lawrence; C. Raina MacIntyre; Brynley P. Hull; Peter B. McIntyre (Elsevier, 2003)
Abstract Objectives:To (i) assess under‐reporting of measles‐mumps‐rubella (MMR) vaccinations to the Australian Childhood Immunisation Register (ACIR); (ii) estimate MMR coverage among five‐year‐old children and the proportion immune to measles infection; (iii) identify factors related to non‐uptake of MMR vaccination. Methods:We analysed ACIR data for a birth cohort of approximately 64,000 children aged five years. The parents of a sample of 506 children with no ACIR record for the second MMR vaccination (MMR2), due at four years of age, were interviewed by telephone to assess under‐reporting to the ACIR and reasons for non‐uptake of MMR vaccination. Results:Parents reported that 22% (n=111) of the surveyed 506 children had received MMR2 before their fifth birthday, and 42% (n=214) by ˜5.5 years of age. After correcting for this level of underreporting to the ACIR, MMR2 coverage for the entire cohort at five years of age was 52.9% (95% CI 52.3-53.4), and increased to 84.1% (95% CI 83.4-84.8) by ˜5.5 years of age. This was 4.3% and 8.2%, respectively, higher than ACIR coverage estimates at the two ages. Based on the corrected MMR coverage estimates, 93% of the cohort was immune to measles due to vaccination. The most common parent‐reported reason for incomplete vaccination was lack of knowledge about the MMR vaccination schedule. Conclusions:Measles elimination in Australia will require continued effort in vaccination coverage and timeliness among pre‐school children. School‐entry requirements are important for MMR2 uptake. Strategies are needed to improve reporting to the ACIR for more accurate measurement of coverage.